Penerapan Permainan Olahraga Bocce Untuk Meningkatkan Minat Berolahraga Terhadap ABK Tunagrahita Pada SLBN 1 Lombok Timur - ; gipari, abdul (Universitas Negeri Jakarta, 2021)
In this study aims to find out whether or not there is an interest in exercising on mentally retarded children in SLBN 1 East Lombok. This type of research uses qualitative methods. In this study the method used to obtain data with a descriptive approach. The population of this research is mild retardation children in SLBN 1 East Lombok with a sample of 20 respondents. The technique of collecting observations and interviews. Analysis of data using descriptive percentages by comparing the results of the first observation with the second with the results of the first observation is 56.56% with sufficient results, the results of the second observation are 75% and the overall observation results with the results of 65.78% with good categories.